Discretization and implementation of a sharp interface model for interfacial heat and mass transfer during bubble growth. (January 2018) - Perez-Raya, Isaac; Kandlikar, Satish G.
Highlights: An algorithm is proposed to estimate the interfacial mass transfer in bubble growth. An algorithm is proposed to find the temperature of cells that have an interface. The mass transfer model is free of interpolation functions and improves accuracy. The model allows a stable simulation with mass transfer only at cells with an interface. The simulation improves the numerical prediction of heat transfer near the interface. Abstract: Simulations of phase change rely on methods to compute heat and mass transfer at the interface. Current methods estimate the mass transfer with interpolation functions or by assuming a local temperature difference between saturation and interface. This work reports a method that uses a single cell around the interface to find the interfacial temperature gradient, and a linear interpolation normal to the interface to find the temperature of the mixture cell (cell with an interface). The one-cell algorithm for sharp interface and mass transfer (OCASIMAT) simplifies the estimation of the mass transfer and mixture cell temperature and improves accuracy. The proposed approach leads to a more realistic representation of the heat and mass transfer at the interface with a sharp discontinuity on the thermal properties at the interface and with mass transfer only at the cells with an interface. Simulations of planar interface evaporation and spherical bubble growth demonstrate the application of the proposed approach. Results indicate that OCASIMAT accurately predicts the temperature distributions near the interface and the interface displacements.